EFFECTIVENESS OF TANDEM EXERCISE ON RISK OF FALL AMONG OLDER PEOPLE - Santoso, Nindita Kumalawati; Yulitasari, Brune Indah; Indrayana, Sofyan; Puspitasari, Desi Wahyu (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The older people population in Indonesia is predicted to continue to increase over the year. Increasing the number of older people will be a challenge for all. Older people might have decreased in the physiological body, especially in balance control such as changes in posture, changes in muscle strength, and visual decline. Balance disorder will increase the risk of falls caused and may result in the elderly being more susceptible to various diseases. Balance exercise such as Tandem Exercise is one way to reduce risk of fall. This research aimed to find out the effect of Tandem exercises on the risk of falling on the older people in Yogyakarta. This research was a Quasy Experimental study With Non-Equivalent Control Group Research Design. Samples of this study were 36 older people trough purposive sampling technique and divided into two groups. Group 1 was given 15 minutes Tandem exercise, every day in two weeks. Group 2 was a control group. The risk of fall was measured by The Time Up and Go Test. This study found that mean score of group 1 was decrease after intervention. This study also found that there was no significant different mean score of fall risk between two groups before intervention (p>0,05), meanwhile there was a significant different mean score after intervention (p<0,05). A significant different on risk of fall score before and after intervention also found in group 1 (p<0,05). In conclusion, health care provider should facilitate older people to participate in balance exercise such as Tandem exercise actively to decrease fall risk among older people.